Car service booking system for Daihatsu Motor Malaysia (DMM) Service Centre - Ummi Amirah, Mohammad Mansor (2019)
The current practice of booking procedure in DMM Sales Sdn Bhd is based on manual booking, where their customer needs to make a telephone call only in business hours to book for a time slot. This procedure caused difficulties to both DMM customer and staff. Therefore, Car Service Booking System (CSBS) is proposed and developed which aim to provide a facility for a web-based car servicing booking system. The customers able to manage their own booking process by selecting the required time slot at the website. This can be done at any time or place as long as the customer has internet facility to complete the booking process. They also able to update or cancel if changes of booking are required through CSBS website without making phone calls to the company. The methodology implemented for this project is Rapid Application Development (RAD) since it speeds up the development and obtain feedback from users at early stage. Once the application is completed, it is tested to the client for user acceptance test (UAT) to ensure that all function work according to the given requirements. The UAT disclosed that the proposed application system has achieved the objective and able to solve the problem of manual as faced.